Governança global dos sistemas alimentares e da segurança alimentar: uma análise crítica do complexo de regimes - Dutra, Thaís Mingoti (2024)
This article addresses the global problem of hunger in contrast to the increasing availability of food. It aims to provide an analysis of current food systems, pointing out their precariousness and their impact on people and the environment. Based on the conceptualization and analysis of the global governance of food systems and the global governance of food security, this article proposes a critical reflection on the relationship between these agendas based on the regime complex approach and highlights the ineffectiveness of the current model in the fight against global hunger. It argues that private actors gain power in governance, which allows them to project their influence on food-related agendas, in a way that perpetuates human rights violations. Finally, this article contextualizes and discusses the climate issue as an aggravating factor in the global food issue